The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1037/0022-006x.62.3.645
|View full text |Cite
|
Sign up to set email alerts
|

Family-based treatment for childhood antisocial behavior: Experimental influences on dropout and engagement.

Abstract: Antisocial behavior in childhood and adolescence is an unquestionably serious problem for society. Family-based treatments are promising but face the challenging obstacle of premature parental dropout. To systematically study dropout, we randomly assigned 147 families with a markedly aggressive child (age 4 to 9 years) to a standard family treatment (SFT) focusing exclusively on parental management or to an enhanced family treatment (EFT) that also promoted frequent discussions of adult issues. EFT produced a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
214
0
14

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(245 citation statements)
references
References 20 publications
13
214
0
14
Order By: Relevance
“…Data indicated that single mothers in the STEPP program attended significantly more treatment sessions compared to single mothers in the traditional BPT program. Of importance, the attendance rate in the STEPP program group compares favorably to other studies that have focused on enhancing attendance to BPT (e.g., Nock & Kazdin, 2005;Prinz & Miller, 1994). However, unlike these studies, which provided enhancements to improve retention in BPT for a general sample of families, our study targeted a population at high risk for poor attendance to BPT.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Data indicated that single mothers in the STEPP program attended significantly more treatment sessions compared to single mothers in the traditional BPT program. Of importance, the attendance rate in the STEPP program group compares favorably to other studies that have focused on enhancing attendance to BPT (e.g., Nock & Kazdin, 2005;Prinz & Miller, 1994). However, unlike these studies, which provided enhancements to improve retention in BPT for a general sample of families, our study targeted a population at high risk for poor attendance to BPT.…”
Section: Discussionmentioning
confidence: 79%
“…Also, the STEPP program incorporates a systematic, problemsolving treatment method (D'Zurilla & Nezu, 1999) to address parent-initiated problems (e.g., time management, conflicts with relatives) that may either interfere with their parenting or affect parents' psychosocial functioning (Kazdin & Whitley, 2003;Pfiffner et al, 1990;Prinz & Miller, 1994;Spaccarelli, Cotler, & Penman, 1992). In addition, the STEPP program incorporates parent-child interactions within the children's social skills group to enhance parenting skill acquisition and a child motivation enhancement within the children's social skills group to provide children incentives for attaining withinsession and home-based behavioral goals.…”
Section: Enhancing Behavioral Parent Trainingmentioning
confidence: 99%
“…Ainsi, plusieurs études ont associé un statut socioéconomique (SSE) défavorisé et l'arrêt précoce du traitement (Armbruster & Fallon, 1994;Fernandez & Eyberg, 2009;Prinz & Miller, 1994;, d'autres concluent au contraire qu'il n'y a pas d'association entre ces deux variables (Kaminer et al, 1992;King et al, 1997;Lazaratou et al, 2000). La définition opérationnelle du SSE varie cependant d'une étude à l'autre.…”
Section: Statut Socioéconomiqueunclassified
“…Les raisons invoquées ont été 1) la croyance que leur enfant ne nécessitait pas de soins psychiatriques (55.3 %), 2) l'impression que l'enfant avait fait des progrès (39.5 %) et 3) un désaccord avec l'opinion clinique du médecin (36.7 %). D'autres études montrent que l'attitude des parents par rapport au traitement peut en influencer la poursuite ou l'arrêt Fernandez & Eyberg, 2009;Luk, Staiger, Mathai, Wong, Birleson, & Adler, 2001;McKay, Harrison, Gonzales, Kim, & Quintana, 2002;Pekarik, 1992;Prinz & Miller, 1994;Zagayko, 1994). Cette variable a été identifiée comme étant la plus significativement associée à l'abandon du traitement chez les adolescents .…”
Section: Expérience Subjective Des Soinsunclassified
See 1 more Smart Citation